A Study of Remaining Lifetime Assessment of Generator Step-up Transformer Using Degree of Polymerization - Surin Sermsukroongsakul (2019)
© 2019 IEEE. This paper presents remaining life study of Generator Step-Up (GSU) transformer in Electricity Generating Authority of Thailand (EGAT). The remaining life of GSU transformer depends on its insulation. The strength analysis of sampling insulation and statistical analysis are used to find aging model. By this life assessment method, it can maintain reliability of generation and transmission system and support Thailand Power Development Plan (PDP) for life extension planning of some power plants. These GSU transformer aging model are assessed and compared with grid transformer aging model in EGAT.